Evaluation of Learning in Civil Engineering Study Program Groups in the Field of Science and Environment in the 21st Century Learning System - Purwaamijaya, Iskandar Muda; Masri, Rina Marina (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
This article aims to evaluate group learning in the field of Civil Engineering and environmental science in the 21st-century learning system. The 21st-century learning system is designed for the 21st-century generation to keep up with the latest technological developments. Survey and mapping learning systems in pandemic conditions have adopted and implemented 21st-century learning systems, but detailed and precise information has not been studied. The research method used is the descriptive quantitative method. The participants of this study are Civil Engineering students. The pretest and posttest questions were used to collect data related to the comprehension test by giving a test via the google form link. The results showed an increase in understanding of the 21st-century learning system. The value of Civil Engineering students' knowledge about the 21st-century learning system increased. This illustrates that delivering material about the 21st-century learning system is quite successful. Thus, there is a need for advanced research on 21st-century learning related to personnel, equipment, and funding.